2018
DOI: 10.1108/ijopm-03-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

How do national cultures impact the operations strategy process?

Abstract: Purpose The purpose of this paper is to analyze the extent to which different patterns of cross-functional integration and the operations strategy (OS) process may be explained by national cultures differences. Design/methodology/approach Perceptual survey data from 105 manufacturing plants in four countries were used to validate the constructs and to test the hypotheses. The plants are located in two Western and two Eastern countries with different industrialization and development backgrounds (Brazil, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 110 publications
0
14
1
Order By: Relevance
“…According to (Minkov et al, 2017), on the scores of the collectivism/individualism dimension, it is found that Brazil, Russia, China, and India are collectivist societies. While a study done by (Beugelsdijk & Welzel, 2018;Lee Park & Paiva, 2018) indicate that Brazil has shifted toward individualism, while there is a consistent result for Russia, China and India for collectivism. Further analysis has been adopted from Hofstede Insight (https://www.hofstede-insights.com) to analyze the cultural dimension among BRIC members.…”
Section: Bric and Hofstede Cultural Dimensionmentioning
confidence: 95%
“…According to (Minkov et al, 2017), on the scores of the collectivism/individualism dimension, it is found that Brazil, Russia, China, and India are collectivist societies. While a study done by (Beugelsdijk & Welzel, 2018;Lee Park & Paiva, 2018) indicate that Brazil has shifted toward individualism, while there is a consistent result for Russia, China and India for collectivism. Further analysis has been adopted from Hofstede Insight (https://www.hofstede-insights.com) to analyze the cultural dimension among BRIC members.…”
Section: Bric and Hofstede Cultural Dimensionmentioning
confidence: 95%
“…The alpha coefficients for all variables were between .710 and .901, which met the suggested threshold of .70 or higher [79], [80]. Next, Confirmatory Factor Analysis (CFA) was conducted to test the construct validity [81]. The CFA results (Chi-square = 381.183; d.f.…”
Section: A Testing Of Scale Reliability and Validitymentioning
confidence: 99%
“…Scholars argue that OM problems due to cultural issues can seldom be generalised. They offer evidence that culture matters for a wide range of operational decisions, and conclude that OM decisions must therefore account for cultural effects (Pagell et al, 2005;Metters et al, 2010;Lee Park and Paiva, 2018). Researchers have identified dimensions…”
Section: Cultural Differences In Ommentioning
confidence: 99%